2003
DOI: 10.1111/j.1527-5299.2002.01219.x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Abnormalities in Chronic Heart Failure Patients: Relation to Exercise Capacity and Therapeutic Implications

Abstract: December 27, 2001; revised July 4, 2002; accepted August 12, 2002 Chronic heart failure (HF) is a common and debilitating condition with high rates of mortality and morbidity. The prevalence of symptomatic HF in the general European population ranges from 0.4%-2% and is expected to increase as the population ages.1 Commonly, symptom generation in chronic HF was attributed to central hemodynamic alterations, but other factors, such as skeletal muscle changes, may also play a role. The purpose of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 60 publications
0
12
0
3
Order By: Relevance
“…This suggests that CHF causes intrinsic defects in skeletal muscles, and numerous studies have reported important functional and biochemical changes in skeletal muscle cells associated with CHF (for recent reviews, see Refs. 202,289,330). These changes may affect fatigue development by acting both on myofibrillar function and on SR Ca 2ϩ handling (287,288,372,457).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that CHF causes intrinsic defects in skeletal muscles, and numerous studies have reported important functional and biochemical changes in skeletal muscle cells associated with CHF (for recent reviews, see Refs. 202,289,330). These changes may affect fatigue development by acting both on myofibrillar function and on SR Ca 2ϩ handling (287,288,372,457).…”
Section: Discussionmentioning
confidence: 99%
“…114 Physical therapists receive training on the use of NMES during their professional education and must demonstrate competency. The NMES unit is a handheld device that is oftentimes readily available to physical therapists.…”
Section: Functional Neuromuscular Electronic Stimulationmentioning
confidence: 99%
“…The substantial decline in functional capacity is one of the primary and most debilitating consequences of HF. Cardiac function and skeletal [114][115][116][117] and respiratory [118][119][120] myopathy all contribute to fatigue and decreased physical exertion capabilities in the HF population. This is particularly relevant to frail HF patients, in whom functional disability is likely to be advanced.…”
Section: Exercise Recommendations Effects Of Hf On Functional Capacitymentioning
confidence: 99%
“…Em seguida, surgiram estudos que avaliaram alterações metabólicas intrínsecas ao tecido muscular, em especial a taxa de utilização dos fosfatos de alta energia (MANCINI et al, 1989). Com a evolução do conhecimento sobre o tema, atualmente já conhecemos diversas alterações morfofuncionais da musculatura esquelética desencadeadas por um quadro de disfunção cardíaca (NICOLETTI et al, 2003), bem como alguns efeitos do TFA (ADAMS, DORING e SCHULER, 2008;BACURAU et al, 2009). Entretanto, nenhum estudo até o presente momento comparou de forma sistemática os efeitos do TFA em alta intensidade com o TFA em intensidade moderada na musculatura esquelética em situações de disfunção cardíaca.…”
Section: Musculatura Esqueléticaunclassified